2011
DOI: 10.3892/mmr.2011.715
|View full text |Cite
|
Sign up to set email alerts
|

Increased FGFR1 copy number in lung squamous cell carcinomas

Abstract: Abstract. The basic fibroblast growth factor (bFGF), via activation of its receptor, FGFR1, has been postulated to be an important inducer of host stromal response and angiogenesis. More recently, FGFR1 amplifications were investigated using large-scale single nucleotide polymorphism arrays in lung cancer. We hypothesized that FGFR1 overexpression may be correlated with the clinicopathological features of lung cancers. The increased copy number of the FGFR1 gene was analyzed by real-time polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 24 publications
3
25
0
1
Order By: Relevance
“…Clearly, discovering novel oncogenic drivers in NSCLC is paramount for improving current therapy. Recently, the fibroblast growth factor receptor 1 (FGFR1) was identified to be frequently amplified in squamous cell lung cancer (>20% of cases) (4,5) as well as in small-cell lung cancer (6% of cases) (6). However, it is still unknown whether these cells are completely addicted to FGFR1 signaling and whether pharmacologically targeting FGFR1 is effective in inhibiting cancer growth.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, discovering novel oncogenic drivers in NSCLC is paramount for improving current therapy. Recently, the fibroblast growth factor receptor 1 (FGFR1) was identified to be frequently amplified in squamous cell lung cancer (>20% of cases) (4,5) as well as in small-cell lung cancer (6% of cases) (6). However, it is still unknown whether these cells are completely addicted to FGFR1 signaling and whether pharmacologically targeting FGFR1 is effective in inhibiting cancer growth.…”
Section: Introductionmentioning
confidence: 99%
“…We divided our patient cohort into these groups as other studies investigating FGFR1 amplification in non-small cell lung carcinomas include patients with squamous cell carcinoma only 21,22,27 and patients with squamous cell carcinoma, adenocarcinoma, and large cell carcinoma. [23][24][25][26] In addition, we found no significant difference in overall survival in surgically radically treated patients stratified by stage and FGFR1 amplification status. Considering statistically significant results only, most studies 9,21,[24][25][26] reported a lack of a significant relationship between survival and FGFR1 amplification status, in line with our findings.…”
Section: Discussionmentioning
confidence: 69%
“…[23][24][25][26] In addition, we found no significant difference in overall survival in surgically radically treated patients stratified by stage and FGFR1 amplification status. Considering statistically significant results only, most studies 9,21,[24][25][26] reported a lack of a significant relationship between survival and FGFR1 amplification status, in line with our findings. However, two studies did detect an effect of FGFR1 amplification on survival with Kim et al 22 reporting significantly greater risk of recurrence and death for patients with FGFR1-amplified squamous cell carcinoma, whereas Tran et al 23 reported a nonsignificant direction of effect toward longer overall survival for patients with FGFR1-amplified tumors in univariate analysis (P ¼ 0.14), which became significant on multivariate analysis (HR 0.6, P ¼ 0.02).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations